The Role of Religiosity Profit-Sharing Rate and Subjective Norm in Enhancing Saving Intention in Islamic Bank - Sukardi (Department of Islamic Economics, Islamic University of Indonesia, 2022)
Islamic banking is an industry that is highly expected to develop. All parties, from the government, banking practitioners, academics to the public, are expected to participate in developing Islamic banking. Therefore, this study aims to determine the factors that can increase people's intention to save in Islamic banks. This study analyzes the effect of profit-sharing, subjective norms, and religiosity on the intention to save in Islamic banks. The research population is teachers and employees of Muhammadiyah schools throughout Yogyakarta City, with a sample of 100 respondents using a cluster (area) non-random sampling technique. This type of research data is primary data with data collection carried out through questionnaires. This research is quantitative research with analysis using the structural equation model method with smart PLS. The results of the analysis show that the profit-sharing rate and subjective norm have a positive and significant effect on saving intention in Islamic banks. However, religiosity has no significant effect on saving intention in Islamic banks. The results of this study are expected to be able to contribute input to Islamic banking in improving its performance. Keywords: Islamic bank, profit-sharing rate, religiosity, subjective norm